Prerequisites and factors of cooperation of Ukraine in the Black sea region - Копачинська, Галина; Козяр, Олена (Human Geography Journal, 2016)
The main factors and prerequisites ofUkraine’s cooperation are enlightened; the role of Black sea region forUkraineand other international actors is reviewed. Therefore, the importance ofBlack seacoastal area is growing nowadays because of its natural resource potential and transit position. There are lots of factors and prerequisites forUkraine’s cooperation with countries of Black sea region, among them historical, social-economic, political, cultural and religious factors, conflict situation and transit position ofUkraine. Historical factors and prerequisites are in common historic background, which influence on present development and cause common problems. Economic-social diversity of region causes lots of problems, but also a background for mutual cooperation between countries ofBlack searegion. Different levels of economic-social development, different international specialization of countries (agriculture, industry, fuel and energy) create basis for economic and trade cooperation. Also states have common social problems. Due to economic-social cooperation,Ukraineis able to resolve existing problems. Politically this region is also diversified. Some states pursue policy directed at Euro-Atlantic integration, moreover, 3 of them are members of EU and NATO (Greece,Bulgaria,Romania). Simultaneously, some countries have opposite political vector (Armenia,Azerbaijan,Georgia).Ukrainehas special interests in this field of cooperation in the case of adopting practice of EU integration and democratic standardization. Conflict situation is a very special common feature of most countries of Black sea region: Nagorno-Karabakh, Transnistria, Abkhazia,South Ossetiaconflicts, the Kurdish problem.Ukraine’s territory also suffered from external aggression (Donbas,Crimea). All these facts raise up the issue of mutual cooperation betweenUkraineand countries of region aimed at settlement of all disputes and solving conflicts. Cultural and religious factors and prerequisites are in great cultural and religious multitude among countries of region andUkraine. All states are multi-national and multi-religion. There is a clash of civilization in the region, between western and orthodox,Turkeyis separate civilization. According to such cultural and religious variety, there is a field for cooperation betweenUkraineand other states of region targeted to monitoring and prediction of possible crisis. The Black sea region is situated on crossroads of transport routes andUkrainehas a special role in the region. However, despite some shortcomings in transit service ofUkraine, its importance is in a central position within the transport and energy sector and the interest of international actors in cooperation with it in this regard. That is whyUkraine’s cooperation with countries of the region in the transport and energy sectors is important and necessary nowadays.